Animal small intestine submucosa acellular matrix anti-adhesion membrane as well as preparation method and application thereof
By laser treatment and sterilization of the submucosal decellular matrix of the animal small intestine, an anti-adhesion film with reduced thickness and improved degradation performance was prepared, which solved the problems of poor flexibility and long degradation time of existing materials, and achieved rapid repair and degradation effects.
Patent Information
- Application Number
- CN202411696045.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-25
AI Technical Summary
During use, existing anti-adhesion materials have poor flexibility, long degradation time, and may lead to chronic inflammation and foreign body reactions, which are difficult to meet the needs of rapid repair and degradation.
By sterilizing one side of the decellularized matrix of the animal's small intestine submucosal layer with laser treatment under specific conditions, an anti-adhesion membrane with reduced thickness and improved degradation performance was prepared. This membrane can not only guide postoperative wound tissue regeneration, but also prevent adhesions from occurring with other tissues and wounds.
It has achieved the reduction in thickness and improved degradation performance of the anti-adhesion film, which can quickly guide wound repair and prevent adhesion, and is suitable for application scenarios where rapid degradation is required.
Smart Images

Figure CN119587766A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of biomaterials, and in particular to an animal small intestinal submucosal decellularized matrix anti-adhesion membrane and a preparation method and application thereof. Background Art
[0002] Tissue adhesion refers to a pathological state in which the contact surfaces of adjacent tissues or organs are connected by cellulose in scar tissue or new fibrous tissue. Adhesion is the most common surgical complication and can occur in various parts of the body, such as the chest cavity, abdominal cavity, uterine cavity, pericardium, tendons, joints, skin and subcutaneous tissue. For example, 60% to 90% of obstetrics and gynecology patients will develop adhesions after pelvic and abdominal surgery, and about 90% of patients will develop postoperative adhesions after abdominal surgery. Adhesions can cause serious complications and even endanger life.
[0003] Anti-adhesion materials are one of the main ways to prevent and treat tissue adhesion. In recent years, a large number of studies have shown that anti-adhesion materials can play a barrier role, effectively blocking adhesion and preventing adhesion-related adverse events. Ideal anti-adhesion materials should have good biocompatibility, effectively block external tissue invasion, and promote postoperative repair of damaged tissues and easy degradation and absorption.
[0004] Anti-adhesion materials can be divided into thin films and liquids. Thin film anti-adhesion materials are generally sponge-like or film-like, and are mainly made of natural polymer materials such as cellulose derivatives, chitosan and polylactic acid. Such film materials may have hard texture and poor adhesion during use. In addition, the local accumulation of acidic products during the degradation of polylactic acid can easily cause mild aseptic inflammation. Liquid anti-adhesion materials are in the form of gel or solution, and are mainly made of hyaluronic acid, chitosan or solution. Such gels or solutions are easy to flow, and there is a risk of unstable efficacy.
[0005] Bioactive materials, such as small intestinal submucosa (SIS), pericardial tissue, dermal tissue and biological amniotic membrane, are natural extracellular matrix membrane materials. After decellularization and other antigen removal treatments, they have good tissue compatibility, low immunogenicity and good flexibility. They are widely used in soft tissue repair applications such as myocardial tissue, skin tissue, oral tissue, and blood vessels. This type of material can overcome the problems of poor flexibility and inflammation caused by degradation products of other anti-adhesion materials, and is one of the potential ideal anti-adhesion materials. Invention patent CN106983918B discloses an anti-adhesion membrane material prepared by small intestinal submucosa tissue, which can not only play an anti-adhesion barrier role through the smooth surface, but also guide tissue repair through the rough surface porous structure. However, on the one hand, the membrane material prepared by this method is composed of at least two layers of small intestinal submucosa materials, and there may be a risk of stratification during use; on the other hand, the degradation time of the membrane material prepared by this method is relatively long, and it may not be applicable to situations where a faster degradation rate is required. For example, the Expert Consensus on Prevention and Diagnosis of Pelvic and Abdominal Adhesions after Gynecological Surgery (2020 Edition) points out that the critical time period for pelvic and abdominal postoperative adhesion formation and mesothelial repair is 3-5 days. If the degradation is too slow, it may lead to problems such as chronic inflammation and foreign body reaction. Summary of the invention
[0006] In order to solve the above problems, the purpose of the present invention is to provide an animal small intestinal submucosal decellularized matrix anti-adhesion membrane and its preparation method and use. The animal small intestinal submucosal decellularized matrix anti-adhesion membrane has reduced thickness and improved degradation performance, which can not only guide postoperative wound tissue regeneration, but also prevent other tissues from adhering to the wound surface.
[0007] The invention provides an anti-adhesion membrane of an animal small intestinal submucosal decellularized matrix, which is obtained by sterilizing one side of an animal small intestinal submucosal decellularized matrix after laser treatment; the parameters of the laser treatment are as follows: a wavelength of 10 to 400 nm, a frequency of ≥50 kHz, a pulse width of ≤1000 fs, a power of 0.1 to 30 W, a filling processing line spacing of 0.001 to 0.1 mm, and a filling number of 1 to 10 times.
[0008] Furthermore, the parameters of the laser processing are as follows: wavelength is 350-360nm, frequency is 190-210kHz, pulse width is 290-310fs, power is 3-5w, filling processing line spacing is 0.005-0.02mm, and filling times is 4-7 times.
[0009] Further, the parameters of the laser processing are as follows: wavelength of 355nm, frequency of 200kHz, pulse width of 300fs, power of 4w, filling processing line spacing of 0.01mm, filling times of 7 times; or, the parameters of the laser processing are as follows: wavelength of 355nm, frequency of 200kHz, pulse width of 300fs, filling processing line spacing of 0.01mm, filling times of 7 times, disordered filling, and power randomly changing in the range of 0.1 to 30w.
[0010] In the present invention, fs means femtosecond, 10 -15 s.
[0011] Furthermore, the sterilization is sterilization by gamma ray irradiation, and the dose of the irradiation sterilization is preferably 15 to 25 KGy.
[0012] Furthermore, the method for preparing the decellularized matrix of the animal small intestinal submucosal layer comprises the following steps: taking the animal small intestinal submucosal layer tissue, inactivating the virus, washing, removing the antigen, washing, and drying to obtain the animal small intestinal submucosal layer decellularized matrix;
[0013] And / or, the animal is a mammal, preferably a pig or a cow.
[0014] Furthermore, the cleaning before antigen removal includes the following steps: washing with water and draining the water. The water is purified water with a pH value ranging from 6 to 8.
[0015] Furthermore, the cleaning before antigen removal is to clean the sample until the conductivity is below 10 μS / cm.
[0016] Furthermore, the cleaning after antigen removal includes the following steps: cleaning with water. The water is purified water with a pH value ranging from 6 to 8.
[0017] Furthermore, the cleaning after antigen removal is to clean the sample until the conductivity is below 10 μS / cm.
[0018] Furthermore, the animal small intestinal submucosal tissue is obtained by cleaning the animal small intestinal tissue and removing the mucosal layer, serosal layer and muscular layer;
[0019] The virus inactivation method is to treat the animal small intestinal submucosal tissue with a peracetic acid-ethanol solution; in the peracetic acid-ethanol solution, the volume percentage concentration of peracetic acid is 0.2-2%, the volume percentage concentration of ethanol is 10%-30%, the volume ratio of the peracetic acid-ethanol solution to the animal small intestinal submucosal tissue material is (2-15):1, the treatment time is 2-4 hours, and the temperature is 10-40°C;
[0020] The method for removing antigens is to use a methanol-chloroform mixed solution and a Triton X-100 solution in sequence to perform fat removal and cell removal treatment on the animal small intestinal submucosal tissue; in the methanol-chloroform mixed solution, the volume percentage of methanol is 30% to 70%, the volume percentage of chloroform is 30% to 70%, the volume ratio of the methanol-chloroform mixed solution to the small intestinal submucosal tissue material is (2 to 10):1, the degreasing time is 2 to 6 hours, and the temperature is 30 to 40°C; the mass percentage of the Triton X-100 solution is 0.1% to 5%, the volume ratio of the Triton X-100 solution to the small intestinal submucosal tissue material is (1 to 10):1, the decellularization time is 0.5 to 4 hours, and the temperature is 30 to 40°C.
[0021] Furthermore, in the peracetic acid-ethanol solution, the volume percentage concentration of peracetic acid is 0.5%, the volume percentage concentration of ethanol is 20%, the volume ratio of the peracetic acid-ethanol solution to the animal small intestinal submucosal tissue material is 10:1, the treatment time is 2 hours, and the temperature is 25°C;
[0022] In the methanol-chloroform mixed solution, the volume percentage of methanol is 40%, the volume percentage of chloroform is 60%, the volume ratio of the methanol-chloroform mixed solution to the small intestinal submucosal tissue material is 8:1, the degreasing time is 3 hours, and the temperature is 37°C; the mass percentage of the Triton X-100 solution is 0.3%, the volume ratio of the Triton X-100 solution to the small intestinal submucosal tissue material is 5:1, the decellularization time is 2 hours, and the temperature is 37°C.
[0023] Furthermore, the number of layers of the animal small intestinal submucosal acellular matrix anti-adhesion membrane is ≥1.
[0024] Furthermore, the animal small intestinal submucosal acellular matrix anti-adhesion membrane is a sheet structure, which may include 1 to 8 layers and has a thickness of 0.1 to 1 mm.
[0025] Furthermore, the animal small intestinal submucosal decellularized matrix anti-adhesion membrane comprises a smooth surface and a rough surface, the laser-treated surface is the rough surface, and the non-laser-treated surface is the smooth surface.
[0026] Furthermore, the smooth surface is dense and less porous, and the rough surface is loose and porous.
[0027] Furthermore, the rough surface micropores completely or partially fill the surface.
[0028] Furthermore, the diameter of the micropores on the rough surface is 10 to 500 μm, and the hole depth does not exceed 60% of the material thickness.
[0029] Furthermore, the degradation time of the animal small intestinal submucosal decellularized matrix anti-adhesion membrane is 0.5-3 months.
[0030] Furthermore, the animal small intestinal submucosal decellularized matrix anti-adhesion membrane has a tensile strength greater than 5N and a tearing strength greater than 0.8N.
[0031] The present invention also provides a method for preparing the above-mentioned animal small intestinal submucosal decellularized matrix anti-adhesion membrane, which comprises the following steps: subjecting one side of the animal small intestinal submucosal decellularized matrix to laser treatment and sterilization to obtain the animal small intestinal submucosal decellularized matrix anti-adhesion membrane.
[0032] The present invention also provides the use of the above-mentioned animal small intestinal submucosal decellularized matrix anti-adhesion membrane in the preparation of anti-adhesion tissue repair materials.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The present invention sterilizes the animal small intestinal submucosal decellularized matrix by subjecting one side of the decellularized matrix to laser treatment under specific conditions to obtain an animal small intestinal submucosal decellularized matrix anti-adhesion membrane. The animal small intestinal submucosal decellularized matrix anti-adhesion membrane has reduced thickness and improved degradation performance, which can guide postoperative wound tissue regeneration and prevent other tissues from adhering to the wound surface. It is particularly suitable for situations where the degradation rate of thin sheet materials needs to be further improved, and has broad application prospects in the preparation of anti-adhesion tissue repair materials.
[0035] (2) The animal small intestinal submucosal decellularized matrix anti-adhesion membrane of the present invention has a porous surface after laser treatment, and the adhesion performance is improved, which can improve the stability of the material during use.
[0036] (3) The animal small intestinal submucosal decellularized matrix anti-adhesion membrane of the present invention is a membrane material with a smooth surface and a hairy surface structure. The hairy surface has a porous structure that can support cell growth and guide wound repair, and the smooth surface is dense and smooth and can effectively prevent the invasion of external cells or tissues, thereby playing an anti-adhesion role.
[0037] (4) The present invention adopts advanced femtosecond laser processing technology to achieve non-contact processing of the material surface, without the introduction of pollutants, with extremely small thermal effects and almost no thermal damage to the material surface.
[0038] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0039] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The microstructure SEM photos of the smooth and matte surfaces of the anti-adhesion membrane of the present invention are shown in FIG.
[0041] Figure 2 This is a photograph of the anti-adhesion film obtained in Test Example 1 when the power is 1 W and the filling processing line spacing is 0.005 mm.
[0042] Figure 3 This is a photograph of the anti-adhesion film obtained in Test Example 1 when the power is 4W and the filling processing line spacing is 0.005mm.
[0043] Figure 4 This is a photograph of the anti-adhesion film obtained in Test Example 1 when the power is 7W and the filling processing line spacing is 0.005mm.
[0044] Figure 5 This is a photograph of the anti-adhesion film obtained in Test Example 1 when the power is 4W and the filling processing line spacing is 0.01mm.
[0045] Figure 6 This is a photograph of the anti-adhesion film obtained in Test Example 1 when the power is 4W and the filling processing line spacing is 0.02mm.
[0046] Figure 7 This is a photograph of the anti-adhesion film obtained in Test Example 1 when the power is 7W and the filling processing line spacing is 0.02mm.
[0047] Figure 8 It is the HE staining diagram of the cross section of the anti-adhesion membrane of the present invention and the statistical diagram of thickness change.
[0048] Fig. 9 This is a comparison chart of the changes in the tensile and tearing properties of the anti-adhesion film after laser surface treatment.
[0049] Fig.10 This is a comparison chart of the degradation performance changes of the anti-adhesion membrane after laser surface treatment.
[0050] Fig.11 This is a comparison chart of the changes in the adhesion properties of the anti-adhesion membrane after laser treatment.
[0051] Fig.12 These are the animal test results of the anti-adhesion membrane of the present invention. DETAILED DESCRIPTION
[0052] The reagents and equipment used in the specific embodiments of the present invention are all known products and are obtained by purchasing commercially available products.
[0053] Example 1 Preparation of animal small intestinal submucosal acellular matrix anti-adhesion membrane
[0054] The specific preparation method is as follows:
[0055] (1) Tissue collection and cleaning: The small intestinal tissue of pigs was collected, cleaned and the mucosal layer, serosal layer and muscular layer were removed to obtain the small intestinal submucosal tissue.
[0056] (2) Virus inactivation: The small intestinal submucosal tissue was treated with a peracetic acid-ethanol solution, wherein the volume percentage concentration of peracetic acid was 0.5% and the volume percentage concentration of ethanol was 20%. The volume ratio of peracetic acid-ethanol solution to small intestinal submucosal tissue material was 10:1. The inactivation time was 2 hours and the temperature was 25°C.
[0057] (3) Cleaning: Use purified water to rinse the small intestine repeatedly 5 times, with a water volume of 20L each time.
[0058] (4) Antigen removal: Methanol-chloroform mixture and Triton X-100 solution were used in turn to perform delipidation and decellularization on the small intestinal submucosal tissue. The first methanol-chloroform mixture used contained 40% methanol by volume and 60% chloroform by volume, and the volume ratio of methanol-chloroform mixture to small intestinal submucosal tissue material was 8:1. The delipidation time was 3 hours at a temperature of 37°C. Then, PBS solution (pH = 6-8) was used to prepare a 0.3% TritonX-100 solution by mass, and the volume ratio of TritonX-100 solution to small intestinal submucosal tissue material was 5:1. The decellularization time was 2 hours at a temperature of 37°C.
[0059] (5) Cleaning: Repeat the cleaning with water in an ultrasonic cleaning machine for 5 times, with a cleaning water flow rate of 7 L / min, maintaining a volume ratio of cleaning water to small intestinal submucosal tissue material of 20:1, an ultrasonic cleaning machine frequency of 40 kHz, and a power of 3000 W. After cleaning, gently wipe off excess water by hand to obtain the small intestinal submucosal matrix material.
[0060] (6) Drying: Spread a layer of the small intestinal submucosal matrix material flat, and use a vacuum oven (60°C, 4h) to dry and dehydrate to obtain a decellularized matrix material.
[0061] (7) Three types of membranes were prepared by scanning one side of the decellularized matrix material using three specific parameters of ultraviolet femtosecond laser to form a rough surface.
[0062] The processing parameters of the three UV femtosecond lasers are as follows:
[0063] Ordered processing A: wavelength 355nm, frequency 200khz, pulse width 300fs, power 4w, filling processing line spacing 0.01mm, filling 4 times; the microstructure of the processing surface is as follows Figure 1 and named the sample as “orderly processed A” membrane;
[0064] Ordered processing B: wavelength 355nm, frequency 200khz, pulse width 300fs, power 4w, filling processing line spacing 0.01mm, filling 7 times; the microstructure of the processing surface is as follows Figure 1 and named the sample as “orderly processed B” membrane;
[0065] Disordered processing: wavelength 355nm, frequency 200khz, pulse width 300fs, filling processing line spacing 0.01mm, filling 7 times, disordered filling, power changes randomly in the range of 0.1~30w during processing; the microstructure of the processing surface is as follows Figure 1 , and the sample was named “disordered processing” membrane.
[0066] (8) Sterilization: The membrane was irradiated and sterilized using Co-60 (15 KGy) to obtain the animal small intestinal submucosal acellular matrix anti-adhesion membranes, which were named "ordered processing A" anti-adhesion membrane, "ordered processing B" anti-adhesion membrane, and "random processing" anti-adhesion membrane, respectively.
[0067] Comparative Example 1 Preparation of acellular matrix anti-adhesion membrane of non-processed animal small intestinal submucosal layer
[0068] Referring to the sample preparation method in Example 1, the only difference is that in step (7), laser processing of the decellularized matrix membrane sheet is not used (and the sample is named "non-processed" membrane sheet), and a non-processed animal small intestinal submucosal decellularized matrix anti-adhesion membrane is prepared, which is named "non-processed" anti-adhesion membrane.
[0069] The beneficial effects of the present invention are demonstrated by test examples below.
[0070] Experimental Example 1 Optimization of UV femtosecond laser processing parameters of anti-adhesion film
[0071] The sample preparation method in Example 1 is referred to, except that in step (7), a UV femtosecond laser with different parameters is used to scan and process one side of the decellularized matrix material to prepare an animal small intestinal submucosal decellularized matrix anti-adhesion membrane. The specific parameters of the UV femtosecond laser are set as follows: wavelength 355nm, frequency 200khz, pulse width 300fs, filling times 7, adjustment power (1w / 4w / 7w) and filling processing line spacing (0.005mm / 0.01mm / 0.02mm).
[0072] The processing marks of the animal small intestinal submucosal decellularized matrix anti-adhesion membrane prepared under different parameters were observed to be obvious and whether there was any damage. As shown in Table 1, under the parameters of wavelength 355nm, frequency 200khz, pulse width 300fs, power 4w, filling processing line spacing 0.01mm, and filling 7 times, the prepared animal small intestinal submucosal decellularized matrix anti-adhesion membrane had no damage and the processing marks were the clearest and most obvious.
[0073] Table 1 Effects of different powers and filling processing line spacing on UV femtosecond laser processing of anti-adhesion film
[0074]
[0075] Test Example 2 SEM test results of anti-adhesion film
[0076] 1. Test methods
[0077] The disorderly processed, ordered processed A, and ordered processed B anti-adhesion membrane samples were sprayed with gold for 5 minutes, and the processed area (400X), non-processed area (400X), and the interface (40X) were observed and photographed by SEM.
[0078] 2. Experimental results
[0079] like Figure 1 The SEM images of the processed area, non-processed area and processed interface after laser processing are the anti-adhesion membrane materials prepared by using disordered processing parameters, ordered parameters A and ordered parameters B, respectively. The results show that laser can be used to control and roughen the surface pattern of the anti-adhesion membrane material, increase the surface porosity, and significantly increase the surface roughness. It shows that the anti-adhesion membrane after laser processing prepared in the embodiment of the present invention can be used to prepare the rough surface in contact with the wound surface.
[0080] HE staining results of the anti-adhesion membrane of Experimental Example 3
[0081] 1. Test methods
[0082] Referring to the method of Example 1, three specific parameters of ultraviolet femtosecond lasers were used to scan and process the processing area on one side of the decellularized matrix material to form a rough surface, and the non-processed area was not laser treated. The disordered processing, ordered processing A, and ordered processing B anti-adhesion membrane samples were immersed in wax and embedded, and then the material was sliced, and then conventionally dewaxed to water and stained with hematoxylin for 5-10 minutes, washed with water, differentiated with hydrochloric acid alcohol, ammonia water turned blue and stained with eosin for 3-5 minutes, and then dehydrated with anhydrous ethanol, and finally made the slices transparent with xylene, and the transparent slices were sealed with gum. After the gum was dried, the biofilm material was observed and photographed under a microscope (100x), and the thickness change was statistically analyzed.
[0083] 2. Experimental results
[0084] like Figure 8 The HE image results in a) show that (the processed and non-processed areas are located on the left and right sides of the dotted line, respectively, with the processed surface facing upwards) that there is no thermal damage on the surface of the biofilm material after laser processing, and the thickness is reduced; and as the number of fillings increases, the laser processing shows an obvious thinning effect. The thickness change of the laser processed anti-adhesion film is shown in the following table. Figure 8 As shown in b), the thinning rate of the membrane material processed by the disordered processing and the ordered processing parameters B is about 50%. The above results show that laser processing can be used to thin the biofilm material and regulate the thickness of the membrane.
[0085] Test Example 4 Mechanical properties of anti-adhesion film
[0086] 1. Test methods
[0087] Tensile strength test: Use non-processed, disorderly processed, ordered processed A, and ordered processed B anti-adhesion membrane samples with a specification of 40×40mm for testing. Before the test, soak the sample in physiological saline for 5-10 minutes, then fix it on the fixture of the tensile machine, and set the tensile rate to 50mm / min for testing. The maximum tensile force recorded when the membrane breaks is the tensile strength, repeat 3 times, and calculate the average value to represent the final result.
[0088] Tear strength test: Use an anti-adhesion film with a specification of 10×25mm for testing, and test it in accordance with the test method specified in YY / T1794-2021.
[0089] 2. Experimental results
[0090] Test items Non-processing Disordered processing Orderly processing A Orderly processing B Tensile strength / N 5.54 5.46 5.50 5.43 Tearing strength / N 0.94 0.85 0.89 0.86
[0091] As shown in the table above and Fig. 9 ab) are the tensile strength and tear strength test results of each sample, respectively. Compared with the non-processed samples, the tensile strength and tear strength of each sample did not change much. This shows that compared with the non-processed anti-adhesion membrane material, the mechanical properties of each sample did not change significantly after laser processing. Laser processing has almost no effect on the mechanical properties of biomembrane materials, and can be used to fit defective tissues of various shapes and avoid rupture during treatment.
[0092] Test Example 5 Degradation Performance
[0093] 1. Test methods
[0094] Non-processed, disorderly processed, ordered processed A, and ordered processed B anti-adhesion membrane samples with a specification of 40×40 mm were used for degradation performance testing. The samples were placed in type I collagenase solution (4 mL, 4 mg / mL) and reacted at 37°C for 6 hours. The samples were then taken out and washed twice with purified water, dried, and weighed in a constant weight volumetric flask. Repeat 3 times, and calculate the average value to represent the final result.
[0095] 2. Experimental results
[0096] Fig.10 The results of the degradation performance test of each sample show that compared with the non-processed anti-adhesion membrane material, the degradation performance of each sample after laser processing is improved. Among them, the degradation performance of the anti-adhesion membrane material prepared by disordered processing and ordered processing B parameters is improved by 2-3 times.
[0097] Test Example 6 Adhesion performance of the rough surface of the anti-adhesion film
[0098] 1. Test methods
[0099] Use non-processed, disorderly processed, ordered processed A, and ordered processed B anti-adhesion membrane samples with a specification of 40×40mm for adhesion strength test. Attach the rough surface of one end of the sample to one end of the biological tissue, with an attachment length of 30mm; then fix the other end of the biofilm material and the biological tissue on the clamp of the tensile machine, with a clamping length of 5mm. Set the constant tensile speed of the tensile machine to 50mm / min, start the tensile machine, and record the maximum tensile force when the sample falls off from the biological tissue, which is the adhesion strength. Repeat 3 times, and calculate the average value to represent the final result.
[0100] 2. Experimental results
[0101] Fig.11 The results of the adhesion strength of the rough surface of each sample show that the rough surface formed by laser processing can improve the adhesion performance of the membrane material and biological tissue. Among them, the adhesion strength of the anti-adhesion membrane prepared by disordered processing and ordered processing parameters B increased by 30% to 40%, showing its significant adhesion performance on the wet tissue surface.
[0102] During surgery, suitable adhesion is conducive to the positioning of the membrane material and improves the success rate of surgery. In the application of pelvic and abdominal surgery repair without suture, good adhesion can ensure that the material is close to or wrapped around the wound during the movement of the postoperative patient to avoid falling off and failure. The above results show that the surface adhesion performance of the anti-adhesion membrane prepared by the disordered processing and ordered processing B parameters of the present invention is significantly improved, which is conducive to improving the treatment effect.
[0103] Test Example 7 Animal Experiment on Anti-adhesion Film
[0104] 1. Test methods
[0105] A 4-cm long longitudinal incision was made on the left side of the lower abdomen (above the uterus) of the experimental rabbit to find the left uterus; the left uterus was repeatedly wiped with a blunt surgical blade until the wound surface bled to form an intrauterine adhesion model. The adhesion model was treated with the hair side of the membrane without any membrane material (positive control), the membrane without laser treatment (non-processing), and the membrane with laser single-side treatment (ordered processing B). The membrane material was fixed to the treatment area of the above three groups of experimental rabbits with absorbable sutures. After the abdominal cavity was moistened with saline, the incisions of the abdominal wall muscle layer and skin layer were sutured continuously layer by layer. The degradation and adhesion of the samples were observed at each sampling time, and photographed and recorded.
[0106] 2. Experimental results
[0107] As shown in Table 2 below, compared with the untreated positive control, no obvious adhesion was found in the area treated with the decellularized matrix of the small intestinal submucosal layer, and the laser single-sided treated membrane (ordered processing B) could be completely degraded in 28 days. Fig.12 As shown, a) is a picture of the sample coated intrauterine adhesion model on day 0, bc) are the results of the laser single-sided treatment membrane (ordered processing B) and the positive control in the experimental rabbit for 28 days, showing that the wound surface of the ordered processing B sample recovered well after treatment and no adhesion occurred, indicating that the anti-adhesion membrane material prepared by laser processing of ordered processing B has good degradation performance and anti-adhesion effect. After the treatment, no inflammation was found in the treatment area and surrounding tissues by naked eye observation, indicating that the degradation product has good tissue compatibility, suggesting the potential for anti-adhesion treatment in vivo.
[0108] Table 2 Evaluation of animal test results
[0109]
Claims
1. An animal small intestinal submucosal acellular matrix anti-adhesion membrane, characterized in that: The method is obtained by sterilizing one side of the decellularized matrix of the submucosal layer of the small intestine of an animal by laser treatment; the parameters of the laser treatment are as follows: wavelength of 10-400nm, frequency ≥50kHz, pulse width ≤1000fs, power of 0.1-30w, filling processing line spacing of 0.001-0.1mm, and filling times of 1-10 times.
2. The animal small intestinal submucosal acellular matrix anti-adhesion membrane according to claim 1, characterized in that: The parameters of the laser processing are as follows: wavelength is 350-360nm, frequency is 190-210kHz, pulse width is 290-310fs, power is 3-5w, filling processing line spacing is 0.005-0.02mm, and filling times is 4-7 times.
3. The animal small intestinal submucosal acellular matrix anti-adhesion membrane according to claim 1, characterized in that: The parameters of the laser processing are as follows: wavelength of 355nm, frequency of 200kHz, pulse width of 300fs, power of 4w, filling processing line spacing of 0.01mm, filling times of 7 times; or, the parameters of the laser processing are as follows: wavelength of 355nm, frequency of 200kHz, pulse width of 300fs, filling processing line spacing of 0.01mm, filling times of 7 times, disordered filling, and power randomly changing in the range of 0.1 to 30w.
4. The animal small intestinal submucosa acellular matrix anti-adhesion membrane according to any one of claims 1 to 3, characterized in that: The sterilization is performed by gamma ray irradiation, and the dose of the irradiation sterilization is preferably 15 to 25 KGy.
5. The animal small intestinal submucosa acellular matrix anti-adhesion membrane according to any one of claims 1 to 3, characterized in that: The method for preparing the decellularized matrix of the animal small intestinal submucosal layer comprises the following steps: taking the animal small intestinal submucosal layer tissue, inactivating the virus, washing, removing the antigen, washing, and drying to obtain the animal small intestinal submucosal layer decellularized matrix; And / or, the animal is a mammal, preferably a pig or a cow.
6. The animal small intestinal submucosal acellular matrix anti-adhesion membrane according to claim 5, characterized in that: The animal small intestinal submucosal tissue is obtained by cleaning the animal small intestinal tissue and removing the mucosal layer, serosal layer and muscular layer; The virus inactivation method is to treat the animal small intestinal submucosal tissue with a peracetic acid-ethanol solution; in the peracetic acid-ethanol solution, the volume percentage concentration of peracetic acid is 0.2-2%, the volume percentage concentration of ethanol is 10%-30%, the volume ratio of the peracetic acid-ethanol solution to the animal small intestinal submucosal tissue material is (2-15):1, the treatment time is 2-4 hours, and the temperature is 10-40°C; The method for removing antigens is to use a methanol-chloroform mixed solution and a Triton X-100 solution in sequence to perform fat removal and cell removal treatment on the animal small intestinal submucosal tissue; in the methanol-chloroform mixed solution, the volume percentage of methanol is 30% to 70%, the volume percentage of chloroform is 30% to 70%, the volume ratio of the methanol-chloroform mixed solution to the small intestinal submucosal tissue material is (2 to 10):1, the degreasing time is 2 to 6 hours, and the temperature is 30 to 40°C; the mass percentage of the Triton X-100 solution is 0.1% to 5%, the volume ratio of the Triton X-100 solution to the small intestinal submucosal tissue material is (1 to 10):1, the decellularization time is 0.5 to 4 hours, and the temperature is 30 to 40°C.
7. The animal small intestinal submucosal acellular matrix anti-adhesion membrane according to claim 6, characterized in that: In the peracetic acid-ethanol solution, the volume percentage concentration of peracetic acid is 0.5%, the volume percentage concentration of ethanol is 20%, the volume ratio of the peracetic acid-ethanol solution to the animal small intestinal submucosal tissue material is 10:1, the treatment time is 2 hours, and the temperature is 25°C; In the methanol-chloroform mixed solution, the volume percentage of methanol is 40%, the volume percentage of chloroform is 60%, the volume ratio of the methanol-chloroform mixed solution to the small intestinal submucosal tissue material is 8:1, the degreasing time is 3 hours, and the temperature is 37°C; the mass percentage of the Triton X-100 solution is 0.3%, the volume ratio of the Triton X-100 solution to the small intestinal submucosal tissue material is 5:1, the decellularization time is 2 hours, and the temperature is 37°C.
8. The animal small intestinal submucosa acellular matrix anti-adhesion membrane according to any one of claims 1 to 3, characterized in that: The number of layers of the animal small intestinal submucosal decellularized matrix anti-adhesion membrane is ≥1.
9. The method for preparing the animal small intestinal submucosal acellular matrix anti-adhesion membrane according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: treating one side of the decellularized matrix of the animal small intestinal submucosal layer with laser, and then sterilizing the decellularized matrix of the animal small intestinal submucosal layer to obtain an anti-adhesion membrane.
10. Use of the animal small intestinal submucosa acellular matrix anti-adhesion membrane according to any one of claims 1 to 8 in the preparation of anti-adhesion tissue repair materials.
Citation Information
Patent Citations
A biological anti-adhesion material, its preparation method and its application
CN106983918B
Anti-adhesion biological membrane and preparation method thereof
CN103405811A
Composite acellular matrix material and preparation method thereof
CN116159185A
Oral cavity restoration film with antibacterial performance and preparation method and application thereof
CN117959502A
Biological membrane as well as preparation method and application thereof
CN118987351A